Identifying Performance Assessment Indicators for Agricultural Small-scale Machinery - М. T. Toshboltaev; Z. O. Muradova (Сельскохозяйственные машины и технологии, 2022)
The use of small-scale machinery proves to be common for agricultural, transportation and other types of work on small-scale farms, peasant farms, family gardens, farmsteads, on hilly lands and inconvenient areas, where the use of traditional powerful machinery is impossible or economically impractical. Small-scale machinery as well as powerful agricultural machinery rarely passes state tests. One of the main reasons for that is a lack of indicator systems for agrotechnical, operational and technological, reliability, economic and ergonomic assessment. The necessity of determining such systems (sets, criteria, indicators) is argued to be important. (Research purpose) The research aims to identify performance assessment indicators for agricultural small-scale machinery by capitalizing on the existing indicators for powerful machines and hands-on experience of exploiting mini-machinery in small farms of Uzbekistan. (Materials and methods) The primary materials are the performance indicators for the agricultural machinery, provided by the existing state and industry standards. The study uses the methods of system analysis, logical thinking, monographic observation and set theory. (Results and discussion) As a result of ranking, several performance indicator systems were selected for the agrotechnical, operational-technological, reliability, economic and ergonomic assessment of small-scale machinery. (Conclusions) It was found out that for the general assessment of the structure parameters, the quality of the technological process and the functionality of small-scale machinery prototypes, it is reasonable to use 26 main and 14 auxiliary indicators. At the same time, a reduction in material and labor resources is expected in the process of testing.